Climate change, ocean acidification and sponges : impacts across multiple levels of organization - Carballo, José Luis; Bell, J. J. (Springer, 2017)
"While sponges represent a very simple group of organisms, which are represented by over 8000 species, there is considerable interest in the increasing role they may play in future marine ecosystems. While we still have a comparatively limited understanding of how sponges will respond to ocean warming and acidification there is evidence that some species may have the ability to acclimate or even adapt to these stressors. This comprehensive collection of articles describes our current understanding of the impacts of ocean acidification and warming on sponges across multiple levels of biological organisation, and from the geological past to the present. With expert contributions from across the world this book represents the most up-to-date view on sponge responses to climate change. This book will be of interest to a wide audience of marine scientists and managers, who are grappling with how to manage, conserve and protect marine ecosystems."-- Provided by publisher.
Keywords: Sponges -- Climatic factors.; Sponges -- Effect of temperature on.; Sponges -- Effect of water acidification on.; elektronické knihy; electronic books